Formation of Social Thought And Freedom of Speech As Socio-Democratic Phenomena (Analysis of Theoretical and Philosophical Concepts) - Aryslanbaevich, Arziev (Pubmedia Social Sciences and Humanities, 2025)
This article explores the evolution of democracy, freedom of speech, and social thought as socio-democratic phenomena through a philosophical and theoretical lens. Tracing their roots from Athenian democracy to modern global practices, the study critically examines how these values are interpreted, implemented, and often manipulated in contemporary politics and media. The paper investigates external and internal factors influencing democratic development, highlights contradictions between democratic ideals and reality, and discusses the interrelation between democracy, civil society, economic freedom, and centralized governance. Emphasis is placed on how global forces, particularly Western political ideologies, shape the discourse and application of democracy in various regions.